2019
DOI: 10.2147/dmso.s215528
|View full text |Cite
|
Sign up to set email alerts
|

<p>Detection of Secondary Metabolites as Biomarkers for the Early Diagnosis and Prevention of Type 2 Diabetes</p>

Abstract: Background: Type 2 diabetes, or T2D, is a metabolic disease that results in insulin resistance. In the present study, we hypothesize that metabolomic analysis in blood samples of T2D patients sharing the same ethnic background can recover new metabolic biomarkers and pathways that elucidate early diagnosis and predict the incidence of T2D. Methods: The study included 34 T2D patients and 33 healthy volunteers recruited between the years 2012 and 2013; the secondary metabolites were extracted from blood samples … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 53 publications
1
7
0
Order By: Relevance
“…Conversely, mannan degradation was markedly decreased. Of interest, serum fucose levels are higher in the T2DM patients compared to healthy cohorts [ 35 ]. Mannan-oligosaccharide in the diet improves the metabolic syndrome in mice, alternatively insulin resistance and dyslipidemia [ 36 , 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, mannan degradation was markedly decreased. Of interest, serum fucose levels are higher in the T2DM patients compared to healthy cohorts [ 35 ]. Mannan-oligosaccharide in the diet improves the metabolic syndrome in mice, alternatively insulin resistance and dyslipidemia [ 36 , 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, elucidating the potential mechanism and identifying potential biomarkers for risk stratification of dysglycemia in CAD is of great clinical importance for disease early diagnosis and prevention. Several studies have revealed the decreased betaine in patients with diabetes than those without [ 32 , 33 ]. So far, no study has discussed the association of circulating betaine with the presence of dysglycemia in CAD.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, elucidating the differences of onset mechanism between T2D and CAD, and identifying sensitive biomarkers for risk predicting of T2D in CAD is of great clinical importance for disease early diagnosis and prevention. Several studies have revealed the decreased betaine in patients with diabetes than those without [32,33]. So far, no study has discussed the association of circulating betaine with risk of T2D in CAD.…”
Section: Discussionmentioning
confidence: 99%